PEMODELAN REGRESI RIDGE PADA KASUS CURAH HUJAN DI KOTA SEMARANG - Maulana Afham; Indah Manfaati Nur; Tiani Wahyu Utami (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Rainfall is the amount of water that falls on the surface of the flat ground for acertain period measured in units of height (mm) above the horizontal surface. Theclassification of rainfall is divided into thick, medium, and light. Based on data of2016 Semarang city rainfall for 6 years experienced a significant decrease andincrease. With the data of rainfall Semarang city is very high potential for flooding.Semarang rainfall data tend to be unstable then it will cause problems in rainfalldata. Therefore it is necessary to solve the problem in rainfall data. The purpose ofthis study is to model and know the factors that affect rainfall in the city ofSemarang. The results of multiple regression found problems in Multicollinearity. An appropriate method for overcoming multiko in multiple regression is the ridgeregression. Regression of ridge to stabilize regression coefficient value of deviationof assumption in Multicolinearity. The result of the research to select the best model using the smallest MSE value which in the regex ridge model has MSE value 1.517smaller than the value of MSE in multiple regression of 1,519. While for variables that have significant effect on rainfall is wind speed, while variable temperature, humidity, solar irradiance have a significant influence but have weak effect on rainfall in Semarang city.Keywords: Rainfall, Ridge Regression and Multiple Regression